Considerations for Occupational Therapists in Developing Community-Level Interventions for Youth with High Adverse Childhood Experiences (ACEs) - Victoria G. Wilburn; Megan Huber; Denise Senter; Hannah B. Stoll (Scholarworks @ WMU, 2022)
Drug misuse likely contributes to the over 30,000 children in foster care and to the 24.2% of children who have experienced two or more adverse childhood experiences (ACEs). Twenty-five percent of children are living in poverty, with nearly half of those living in single-parent households. Among the national guidelines to preventing ACEs are connecting youth with positive activities and providing family relationship enhancement opportunities. We believe the profession of occupational therapy can help contribute to the mental and behavioral health care workforce in a greater capacity than is currently used. Many children are not afforded the opportunity to engage in novel leisure pursuits that are essential for positive mental health function and well-being. Occupational therapists can assist in creating a culture of health and equity for youth by harnessing the power of play and leisure to promote self-healing communities.